PERUBAHAN FUNGSIONAL PENYAKAIT PARKINSON DENGAN MENGGUNAKAN UNIFIED PARKINSONS DISEASE RATING SCALE UPDRS - Herlina Sari*, Salim Harris* , Manfaluthy Hakim*, Yusuf Misbach*, Herqutanto** (NEURONA, 2010)
INTRODUCTION PROGRESSIVE DECLINE IN FUNCTIONAL STATUS IS THE EXPECTED NATURAL COURSE OF PARKINSONS DISEASE THE VARIABILITY BETWEEN PATIENTS MANIFESTED BY INDIVIDUAL PATIENTS MOTORIC FUNCTION AND DISABILITY SEEM TO PROGRESS AT DIFFERENT RATES